Influence of Stacking Order on the Structural and Optical Properties of Cu2ZnSnS4 Absorber Layer Prepared from DC-Sputtered Oxygenated Precursors - Gwaydi, January S; Sawa, Hezekiah B; Rwenyagila, Egidius R; Komba, Nathanael R; Kibona, Talam E; Mlyuka, Nuru R; Samiji, Margaret E; Mwakyusa, Lwitiko P (Tanzania Journal of Science, 2024)
Several studies have attempted to overcome the sudden volume expansion of the precursor during sulfurization by the use of oxygen-containing precursors when growing the CZTS absorber. This work demonstrates the influence of precursor stacking orders on the properties of the CZTS thin film absorber layer from DC-sputtered oxygenated precursors for solar cell applications. CZTS absorber layers were prepared from three types of DC-sputtered stacks, namely, Zn-O/Sn/Cu, Sn/Zn-O/Cu, and Sn/Cu/Zn-O. The precursors were sequentially deposited on a soda lime glass (SLG) using DC-magnetron sputtering and annealed in a sulfur and nitrogen ambient. X-ray diffractometry (XRD) and Raman spectroscopy analyses reveal the formation of crystalline kesterite CZTS structure regardless of the precursor stacking order. Atomic force microscope (AFM) analysis showed that CZTS thin films grown from precursor stacks SLG/Zn-O/Sn/Cu and SLG/Sn/Zn-O/Cu had improved morphological properties with densely packed large grains compared to that with stack SLG/Sn/Cu/Zn-O. SLG/Zn-O/Sn/Cu is the best stack among the studied stacking orders since it exhibits large grains in the absorber layer, which is preferential for high-efficiency thin film solar cells. The use of oxygenated precursor with order Sn/Zn-O/Cu promises improved CZTS absorber properties as it exhibits better morphological properties.